Letramento digital em contextos de autoria na internet - Zulmira Medeiros Roque (2011)
In this research we investigated the constitution of a discursive practice among educators in process of initial training, working in a sociotechnical network, in a virtual learning environment, and in this practice, we sought to understand the relationship between participation in contexts of authorship and the process of digital literacy experienced by these individuals. Our theoretical framework was formed by the concepts of authorship and digital literacy, advancing studies on multimodality and genres. In the field research, we set out to follow the initial training of graduates on Pedagogy at distance, offered by UAB/UFMG that use the MOODLE platform as the virtual learning environment. The subjects to participate in this space were interacting with each other, building and publishing their writing, and in this way, being authors and readers in a sociotechnical network. The methodological framework was based on the guidelines of the language philosophy, with elements of conversational analysis and content analysis to operate the collection and organization of data. At first, knowing the technological profile, we have seen changes in terms of digital literacy displayed by the subjects. Then, following the participation of these subjects in the virtual learning environment and investigating the discursive practices that were formed in the contexts of authorship, we sought to understand how was the relationship of these subjects among themselves and with the virtual multimodal environment through their online writing. At the end, analyzing the conditions of literacy expressed, we could achieve a more explanatory content, concluding that such conditions are given through the appropriation of new genres, enabled by the lived experience of authorship in online contexts. The results showed that the text and the speech produced by these individuals in this environment are modified over time, which are influenced by the relationships that individuals establish among themselves, with the technology and the academic environment. So, appropriation of the genre features the process of literacy experienced by the subject and facilitates their insertion in a particular field of discourse or social sphere. This research, within its limitations, highlights the role of the exercise of authorship in virtual learning environments, recognizing the formation and consolidation of new genres - digital and academic - explained in the interactions between these subjects and with the virtual environment through online writing.